Melanoma inhibitory activity promotes melanoma development through activation of YBX1. (14th June 2013) - Schmid, Rainer; Meyer, Katharina; Spang, Rainer; Schittek, Birgit; Bosserhoff, Anja‐Katrin
Summary Melanoma inhibitory activity (MIA), a small soluble secreted protein, is functionally important for progression of malignant melanoma. We recently revealed that p54nrb acts as a mediator of MIA action. In this study, we characterize the transcriptional regulation of p54nrb by MIA to explain MIA's molecular action. We identified one highly conserved region in the p54nrb promoter that is necessary and sufficient for MIA‐dependent activation. Functional promoter analysis identified the transcription factor YBX1 as the mediator of MIA activation of p54nrb transcription. We screened the genome for further potential MIA‐regulated genes carrying the element in their promoter regions. Integrating our sequence data with expression data from human melanomas identified a list of 23 potential MIA‐YBX1 targets in melanomas. In summary, we present for the first time effects of MIA on transcriptional regulation. Uncovering new potential downstream effectors working via activation of YBX1 supports the important role of MIA in melanoma.